Urgensi Hisab dan Rukyat pasca UU No. 3 Tahun 2006 - Jannah, Sofwan (Al-Mawarid Jurnal Hukum Islam, 2007)
After regulating the Act No. 3 year 2006 concerning enlarging Islamic court jurisdiction. Beside the practical astronomy as a tool or instrument for the validity of Moslem rituals also it motivates the judges of Islamic court in order to own the capacity to understand the beginning of Qomariyah months correctly. Islamic practical astronomy can predict the positions for instance those of sun, moon, earth etc. Thus, the graduations of Syariâah faculty or department have the challenging to study Islamic Economics because the qualification for becoming judge of Islamic court should need much knowledge to handle the cases. Kata kunci: hisab rukyat, peradilan agama, sdm, ekonomi syariâah.